Volume 1: Advances in Solar Buildings and Conservation; Climate Control and the Environment; Alternate Fuels and Infrastructure 2015
DOI: 10.1115/es2015-49354
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Different Operation Strategies for Falling Particle Receivers

Abstract: The potential for highly efficient and cost competitive solar energy collection at high temperatures drives the actual research and development activities for particle tower systems. One promising concept for particle receivers is the falling particle receiver. This paper is related to a particle receiver, in which falling ceramic particles form a particle curtain, which absorbs the concentrated solar radiation. Complex operation strategies will result in higher receiver costs, for both investment and operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Once heated, the particles may be stored in an insulated tank and/or used to heat a secondary working fluid (e.g., steam, CO 2 , air) for the power cycle (see Figure 7). Although a number of analytical and laboratory studies have been performed on the falling particle receiver since its inception in the 1980's [102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118], only one set of on-sun tests of a simple falling particle receiver has been performed [114]. Those preliminary tests, which did not optimize the configuration of the receiver aperture, only achieved 50% thermal efficiency, and the increase in particle temperature was ~250°C from ambient conditions.…”
Section: Solid Particle Receiversmentioning
confidence: 99%
“…Once heated, the particles may be stored in an insulated tank and/or used to heat a secondary working fluid (e.g., steam, CO 2 , air) for the power cycle (see Figure 7). Although a number of analytical and laboratory studies have been performed on the falling particle receiver since its inception in the 1980's [102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118], only one set of on-sun tests of a simple falling particle receiver has been performed [114]. Those preliminary tests, which did not optimize the configuration of the receiver aperture, only achieved 50% thermal efficiency, and the increase in particle temperature was ~250°C from ambient conditions.…”
Section: Solid Particle Receiversmentioning
confidence: 99%
“…Operation strategies of such receivers have been http://dx.doi.org/10.1016/j.solener.2015.06.007 0038-092X/Ó 2015 Elsevier Ltd. All rights reserved. Gobereit et al (2013), who demonstrated that an efficiency in excess of 90% can be reached for a face-down design receiver. The Small Particle Heat Exchanger Receiver (SPHER) concept was demonstrated at lab-scale by Frederickson et al (2014) with a solar simulator: the outlet of the mixed air-CO 2 gas flow reached 800°C.…”
Section: Introductionmentioning
confidence: 97%
“…The majority of those studies focused on modeling the particle hydraulics and radiant heat transfer to falling particles. Various geometries and configurations of falling particle receivers have been considered, including north/south facing cavity receivers as well as face-down cavity receivers with a surrounding heliostat field [8,32,42]. In 2008, Siegel et al performed one of the first onsun tests (in batch mode) of a simple free-falling particle receiver [18,49].…”
Section: Introductionmentioning
confidence: 99%